Analysis Of The Pon 2024 Logos: A Semiotics Study - Siahaan, Lidya Elisca; Sembiring, Rony Arahta; Sihite, Jubil Ezer (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The aim of this study is to determine the type and meaning contained in the PON 2024 Aceh-North Sumatra logo from the perspective of Charles Sanders Peirce's semiotics. A logo is a design element that functions as a visual representation of an entity, such as a company, organization, or product, consisting of a combination of symbols, images, and text designed with unique and distinctive visual elements. The method used is descriptive qualitative. This research will produce descriptive data in the form of written or spoken words from the image objects observed during the research. The results of the research on the PON 2024 Logo show that there are 3 icons, namely the Rencong shape, the Malay Songket Fabric shape, and the Batak Ulos Fabric shape. One index in the form of 5 torches, and one symbol in the form of 3 rings, which symbolizes the parent container of Indonesian sports achievements. The logo also has 5 colors that have meaning for each color (red, yellow, green, white, and black). The PON 2024 logo successfully represents the event by combining local cultural elements that are rich in meaning and symbols that reflect the spirit of sports. With the modern design and deep philosophy, the logo not only functions as a visual identity but also as a symbol of the unity and mutual cooperation of the Indonesian people to make this sporting event a success.